PENGARUH FAKTOR EKONOMI MAKRO TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR INFRASTRUKTUR - Pebi Silpiawati; Diah Yudhawati; Titing Suharti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This research was conducted with the aim of knowing the effect of exchange rates on stock prices, inflation rates on stock prices and interest rates on stock prices of infrastructure sector companies listed on the Indonesia Stock Exchange for the period 2016-2022 individually or simultaneously. The sampling technique uses non-probability sampling purposive sampling category with quantitative data source and secondary data source. Based on the criteria that have been determined, a sample of 7 infrastructure sector companies was obtained as the object of research. The data analysis method used is panel data regression analysis, descriptive statistical analysis, classical assumption test, coefficient of determination analysis along with hypothesis testing. The results obtained from the research indicate that partially the exchange rate and inflation variables have no significant effect on stock prices. While the interest rate variable has a significant effect on stock prices. And simultaneously or together, the variables of exchange rates, inflation and interest rates have a significant influence on the stock prices of infrastructure sector companies for the period 2016-2022.